Problem Penerapan Bagi Hasil dalam Pembiayaan di Perbankan Syariah - Kusumastuti, Dani (Fakultas Syariah IAIN Purwokerto, 2010)
Instead of the rationale and potential benefits of the PLS system emphasized by the academic community, experiences indicate some inherent problems in applying PLS mode of financing. These problems prevent banks from adopting the PLS financing contract, thus there is a lack of profit-loss sharing (PLS) contract in the practice of Islamic banking. Basically, the problems arose from the nature of the system itself, which does not ascertain the rate of return positively, this system gives a wide range of freedom that release the user of the fund to manage and control the activity and productivity of the business. On the other side, it potentially brings Islamic Banks to face to face with the problem of moral hazard and adverse selection done by the user of the fund (businessman). These main problems derived from the existence of asymmetric information between the bank and the user of the fund. To be able to contribute to the economic stability, shariah banking should dominate their financing portfolio based on the PLS system. For that aim, many ways are offered.